2020
DOI: 10.1111/1468-0106.12330
|View full text |Cite
|
Sign up to set email alerts
|

The puzzle of quality upgrading of Chinese exports from the trade liberalization perspective

Abstract: Trade liberalization could accelerate the process of quality upgrading through the competition effect. However, that the quality of Chinese exports exhibits an opposite performance pattern is puzzling. The present paper uses a framework based on multiproduct firms to analyse the mechanism of how the product quality of exports is affected by trade liberalization to explain this puzzle. The model includes two major mechanisms: the competition effect and the market effect. There is a huge gap in the influence on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Their studies show that NTMs have negative impacts on supply chains. Similarly, Ghodsi and Stehrer [23] and Huang et al [24] investigated the role played by NTMs in enhancing product quality and affecting trade, and they found that NTMs help increase the quality of imported goods. Deepika [25] and Luo and Bano [26] studied the impacts of NTMs on export competitiveness, and they show that the implementation of these measures increase firms' production costs in certain sectors and reduce domestic firms' competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their studies show that NTMs have negative impacts on supply chains. Similarly, Ghodsi and Stehrer [23] and Huang et al [24] investigated the role played by NTMs in enhancing product quality and affecting trade, and they found that NTMs help increase the quality of imported goods. Deepika [25] and Luo and Bano [26] studied the impacts of NTMs on export competitiveness, and they show that the implementation of these measures increase firms' production costs in certain sectors and reduce domestic firms' competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A sizeable literature has been published on the impacts of NTMs on trade [4,[14][15][16][17][18][19][20]. Most research has tended to focus on the implications of NTMs in general, and hence, several current studies have shifted attention to NTMs with specific purposes: improving supply chains [21,22], enhancing quality [23,24], and increasing export competitiveness [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive tax incentives may promote output and export expansion, which could lead to a crowding out of human capital and a weakening of the quality of export products [24]. Trade liberalization will also promote the quality of export products, and the impact on the quality of export products is heterogeneous among different types of enterprises [25]. In terms of transmission mechanisms, trade liberalization can contribute to the quality of export products through increased competition [26], quality upgrading of intermediate inputs, and productivity gains [27].…”
Section: Literature Reviewmentioning
confidence: 99%